Self-actuated biomimetic nanocomposites for photothermal therapy and PD-L1 immunosuppression - Li, Wenxin; Li, Fen; Li, Tao; Zhang, Wenyue; Li, Binglin; Liu, Kunrui; Lun, Xiaoli; Guo, Yingshu (Frontiers in Chemistry, 2023)
Due to the particularity of tumor microenvironment (TME), the effect of various tumor treatments is limited. We designed and synthesized a multifunctional treatment platform (PB/PM/HRP/Apt) with unique working mechanism and good tumor treatment effect. Prussian blue nanoparticles (PBs) were used as the core and coated with platelet membrane (PM). As a photothermal agent (PTA) with good photothermal conversion efficiency, PBs obtains good photothermal performance under near-infrared light irradiation. The ability of platelets (PLTs) to specifically target cancer cells and sites of inflammation can effectively enhance PB aggregation at tumor sites. Then, the surface of the synthesized nanocomposite was modified with horseradish peroxidase (HRP). The presence of HRP leads to the decomposition of hydrogen peroxide in the TME, thereby enhancing the deep penetration of nanocomposites in cancer cells. Finally, modification of PD-L1 aptamer and 4T1 cell aptamer AS1411 on nanocomposites can achieve immunotherapy and enhance targeting. PB/PM/HRP/Apt not only has good targeting and biocompatibility, but also has the ability to deliver PTA to cancer cells as completely as possible. Moreover, the combination of photothermal therapy (PTT) and immune blocking agents can also cause strong immune response, which greatly improves the tumor killing ability. Most importantly, HRP loading significantly improved the transport efficiency of nanocomposites and facilitated their aggregation at tumor sites. As a promising therapeutic strategy, this biomimetic nanoplatform provides new inspiration for current cancer diagnosis and treatment.